2010
DOI: 10.1039/b913482d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the phase behavior of ionic liquids in organically functionalized silica ionogels

Abstract: We have synthesized mesoporous silica monoliths functionalized with 2-(4-pyridylethyl)triethoxysilane 1 and N,N-dimethyl-pyridine-4-yl-(3-triethoxysilyl-propyl)-ammonium iodide 2. The organically modified silica monoliths were characterized via IR spectroscopy, nitrogen sorption, small angle X-ray scattering (SAXS), thermogravimetric analysis-differential thermal analysis (TGA-DTA), and acid-base titration. The degree of functionalization can be changed by the ratio of the functional silane to the silica precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 28 publications
6
51
2
Order By: Relevance
“…In general, the confinement of IL by a non-conducting support, such as SiO 2 , results in a decrease in thermal stability [18]. However, for ILs that show strong interaction with the support, an increase in thermal stability is observed [17,19]. In our systems, the stronger interaction of EZT3 with the support in S15-10 and -25 (compared with S15-50 and -80) as manifested in the frequency shifts (vide supra) and the monotonic spreading of the IL on the pore walls (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…In general, the confinement of IL by a non-conducting support, such as SiO 2 , results in a decrease in thermal stability [18]. However, for ILs that show strong interaction with the support, an increase in thermal stability is observed [17,19]. In our systems, the stronger interaction of EZT3 with the support in S15-10 and -25 (compared with S15-50 and -80) as manifested in the frequency shifts (vide supra) and the monotonic spreading of the IL on the pore walls (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…[41][42][43] Recently, Gçbel et al [44] have studied the DSC, NMR and IR spectra obtained from inserting 4 ] etc) in silica of different pore sizes, which was achieved by varying base catalysts like pyridine, 3-fluoropyridine and 2-picoline. More recently Gçbel et al [45] obtained IL-silica monoliths of different pore sizes by functionalizing the silica pore walls by adding N,N-dimethyl-pyridine-4-yl-(3-triethoxysilylpropyl)-ammonium iodide and 3-fluoropyridine and 2-(4-pyridylethyl)triethoxysilane in TMOS in different ratios. Functionalization [45] of silica matrix was also found to affect the phase behavior of confined IL.…”
mentioning
confidence: 98%
“…More recently Gçbel et al [45] obtained IL-silica monoliths of different pore sizes by functionalizing the silica pore walls by adding N,N-dimethyl-pyridine-4-yl-(3-triethoxysilylpropyl)-ammonium iodide and 3-fluoropyridine and 2-(4-pyridylethyl)triethoxysilane in TMOS in different ratios. Functionalization [45] of silica matrix was also found to affect the phase behavior of confined IL. Gçbel et al [44] showed from DSC studies that in restrictive geometry, the melting point of [EMIM] based ILs decreases by~8 to 148C.…”
mentioning
confidence: 98%
“…Moreover, the shape of the PSD and the position of the mean were preserved, with the decrease in peak intensity indicating the presence of the adsorbed IL layer only. 55,56 Singh et al 47 and Gobel et al 57 both observed the reduction in thermal stability upon confinement of IL into porous substrates. If we assume an ideal case where all the EZT3 penetrates the pores, the pore volume lost due to impregnation (V p,lost ) would be equal to the volume of the EZT3 (V EZT3 ) loaded.…”
Section: Discussionmentioning
confidence: 99%